PERBEDAAN KONSTRUKSI PEMBERITAAN TIMNAS INDONESIA TENTANG PIALA AFF U22 PADA CHANNEL YOUTUBE METRO TV DAN TV ONE JELANG PILPRES 2019 - Rahmawan, Khairul; Kartinawati, Erwin; Wiryawan, Hari (JURNAL KOMUNITAS, 2022)
The Differences in framing news for the Indonesia National Team Winning the AFF U-22 Cup on Youtube Channel Metro TV and TV One before the 2019 Presidentian Election. This study aims to describe how the differences in franing news carried out by the two media are related to issues of appreciation and meetings President Jokowi with the U-22 National Team. The research method is descriptive qualitative with the Pan and Kosicki framing analysis. These results of this study indicate that the news presented by Metro TV on the youtube channel wants to povide a positive image of the government, especially Jokowi’s figure as a president who cares about Indonesia football by looking at the syntacsis and rhetorical structure of Metro TV news. Meanwhile, TV One on its YouTube channel emphasizes the U-22 national team’s struggle to win the AFF championship and focuses on facing the next tournaments.